ANALISIS PEMILIHAN SUPPLIER OBAT PADA APOTEK ADINDA MENGGUNAKAN METODE ANALYTICAL HIERARCHY PROCESS (AHP) - Rosyiidi, Thoriqi; Subagyo, Ade Momon (Inaque : Journal of Industrial and Quality Engineering, 2021)
In this study, researchers used the Analytical Hierarchy Process (AHP) method as a decision support tool in supplier selection. This research is expected to be able to provide information to the Adinda Pharmacy regarding which supplier should be chosen to be the top priority in meeting the needs of the pharmacy. This method starts from identifying problems that occur at the pharmacy, after which the criteria that are considered important are determined through preliminary interviews and filling out questionnaires by the pharmacy. Data processing was done using Microsoft Excel. Sampling used in this study using purposive sampling technique. The number of samples used in this study were 5 suppliers. From the research results, the level of importance of the most influential criteria in supplier selection is the quality criteria with a weight value of 0.51. Second, the price criteria (0.23). Third, the service criteria (0.13). Fourth, the delivery criteria (0.08). Fifth, quantity criteria (0.05) with a consistency ratio test value of 0.06. This shows that Apotek Adinda prioritizes high quality products from suppliers. The results obtained from research using the Analytical Hierarchy Process method are the priority order of the best drug suppliers for Adinda Pharmacy, namely PT. Marganusantara Jaya with a weight value of 0.38. Keywords: Supplier Selection, Analytical Hierarchy Process, Best Supplier